Characterization of the bacterial microbiome among free-ranging bottlenose dolphins (Tursiops truncatus). Issue 6 (June 2020) - Robles-Malagamba, María José; Walsh, Michael T.; Ahasan, Mohammad Shamim; Thompson, Patrick; Wells, Randall S.; Jobin, Christian; Fodor, Anthony A.; Winglee, Kathryn; Waltzek, Thomas B.
Abstract: Marine animals represent a dynamic and complex habitat for diverse microbial communities. The microbiota associated with bottlenose dolphins ( Tursiops truncatus ) are believed to influence their health status, but it remains poorly understood. We therefore characterized and compared the bacterial microbiome of bottlenose dolphins from six different anatomical sites that represent four different body systems (respiratory, digestive, reproductive, and integumentary). In this study, a total of 14 free-ranging bottlenose dolphins were sampled during the 2015 Sarasota Bay Dolphin Health Assessment. Bacterial diversity and abundance were assessed by PCR amplification of the hypervariable V3–V4 regions of the bacterial 16S rRNA gene for each sample, followed by sequencing on an Illumina MiSeq platform. Analysis showed that bottlenose dolphins harbor diverse bacterial communities with a unique microbial community at each body system. Additionally, the bottlenose dolphin bacterial microbiome was clearly distinct to the aquatic microbiome from their surrounding habitat. These results are in close agreement with other cetacean microbiome studies, while our study is the first to explore what was found to be a diverse bottlenose dolphin genital microbiome. The core bacterial communities identified in this study in apparently healthy animals might be informative for future health monitoring of bottlenose dolphins. Abstract : Microbiology; Biological sciences; Veterinary medicine; Health sciences; Bottlenose dolphin; Microbiome; Next-generation sequencing; Health assessment.